MULTICULTURAL ISLAMIC EDUCATION BASED ON RELIGIOUS TRADITION AND LOCAL CULTURE AT PESANTREN MAMBAUL FALAH BAWEAN GRESIK - Ahmad Halid; Anis Rofi Hidayah (Universitas Islam Malang, 2022)
Multicultural education is an educational and learning process that aims to develop all student potential with a learning model of appreciating, appreciating the diversity of students' backgrounds and heterogeneity as a form of diversity in traditions, local culture, ethnicity, ethnic differences, and the many sects in religion, differences in students' potential , talent different interests. So it needs to be achieved through multicultural learning. Islamic Multicultural Education at pesantren Mambaul Falah Bawean Gresik is carried out referring to the religious traditions and local culture of the pesantren. The problem of this research is how is the implementation of Islamic multicultural education based on religious and cultural traditions at the Pesantren Mambaul Falah Tambilung Tambak Bawean Gresik? This problem was solved by using qualitative methods, descriptive analysis and methods of collecting data using observation, interviews and documentation. The implementation of Islamic multicultural education based on religious and cultural traditions at the Mambaul Falah Islamic Boarding School is carried out in six steps, namely (1) Strengthening Islamic Boarding School religious traditions, (2) the yellow book, (3) santri character, (4) santri culture, (5) local culture, (6) religious practice values.